COVID-19 living evidence profile #5 (version 5.1): What went well and what could have gone better in the COVID-19 response in other countries, as well as what will need to go well in future given any available foresight work being conducted? - Waddell, K; Wilson, MG; Bain, T; Bhuiya, AR; Al-Khateeb, S; Sharma, K; DeMaio, P; Lavis, JN (My University, 2021)
An overview of the best available research evidence from around the world (i.e., evidence syntheses) and local research evidence (i.e., single studies) and, if applicable, a scan of experiences from other countries and from Canadian provinces and territories, about what went well and what could have gone better in the COVID-19 response in other countries, as well as what will need to go well in future given any available foresight work being conducted in response to a decision-maker’s request.
Keywords: COVID-19; response; countries; future; foresight; work